2002
DOI: 10.4049/jimmunol.169.6.2842
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Thymocyte-Independent and Thymocyte-Dependent Phases of Epithelial Patterning in the Fetal Thymus

Abstract: Thymic epithelial cells (TECs) in adult mice have been classified into distinct subsets based on keratin expression profiles. To explore the emergence of TEC subsets during ontogeny, we analyzed keratin 8 and keratin 5 expression at several stages of fetal development in normal C57BL/6J mice. In addition, thymic epithelial development and compartmentalization were explored in recombination-activating gene 2/common cytokine receptor γ-chain-deficient and Ikaros-null mice that sustain early and profound blocks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
164
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(182 citation statements)
references
References 29 publications
15
164
0
3
Order By: Relevance
“…As shown in Figure 2a-c and in agreement with the literature (Klug et al, 1998), we observed prominent expression of K5 by medullary TE and a small subset of cortical TE in WT thymus, with the majority of the cortical TE expressing a K8 ϩ K5 Ϫ phenotype. We found K8 expression to be more widespread among medullary TE than has been previously reported (Klug et al, 1998(Klug et al, , 2002 and observed that most of the medullary TE was K5 ϩ K8 ϩ . As described previously (Klug et al, 1998), K14 expression was more restricted to medullary TE in the WT thymus when compared with K5; few cortical TE were K8 ϩ K14 ϩ , and the corticomedullary boundary of K14 expression was more distinct than that of K5 ( Fig.…”
Section: Patterns Of Keratin Expression By Te Are Altered In the Lckfsupporting
confidence: 53%
See 1 more Smart Citation
“…As shown in Figure 2a-c and in agreement with the literature (Klug et al, 1998), we observed prominent expression of K5 by medullary TE and a small subset of cortical TE in WT thymus, with the majority of the cortical TE expressing a K8 ϩ K5 Ϫ phenotype. We found K8 expression to be more widespread among medullary TE than has been previously reported (Klug et al, 1998(Klug et al, , 2002 and observed that most of the medullary TE was K5 ϩ K8 ϩ . As described previously (Klug et al, 1998), K14 expression was more restricted to medullary TE in the WT thymus when compared with K5; few cortical TE were K8 ϩ K14 ϩ , and the corticomedullary boundary of K14 expression was more distinct than that of K5 ( Fig.…”
Section: Patterns Of Keratin Expression By Te Are Altered In the Lckfsupporting
confidence: 53%
“…The basis for differences in K8 expression by medullary TE reported here and elsewhere (Klug et al, 1998(Klug et al, , 2002 is not obvious and may reflect the use of different fluorochomes (FITC vs. Alexa 488) or differences in instrumentation. Furthermore, because shifts in fluorescence color (green ϩ red 3 yellow) are very dependent on the relative intensity of the fluorescence signals involved, these spectral shifts may not accurately reflect the true extent of colocalization.…”
Section: Discussionmentioning
confidence: 60%
“…On a per-cell basis, CII expression was again reduced in Ltbr Ϫ/Ϫ mTECs relative to WT with GAPDH as internal control (data not shown). Furthermore, because K14 is specifically and constitutively expressed in the majority of mTECs (5,20). K14 was used as an internal control in real-time PCR, CII expression remained reduced in Ltbr Ϫ/Ϫ mTECs relative to WT (Fig.…”
Section: Thymic Expression Of CII Is Controlled By Ltmentioning
confidence: 99%
“…The early TECs generated during embryogenesis contain bipotent progenitor thymic epithelial cells (pTECs) that are capable of generating both cTECs and mTECs [2,3]. It is acknowledged that thymocyte development differentially affects cTEC development [4][5][6] and mTEC development [7,8]. However, how pTECs branch into cTECs and mTECs and what regulates their developmental pathways are not fully understood.…”
Section: Cortical Thymic Epithelial Cells (Ctecs) and Medullary Thymimentioning
confidence: 99%